Optically induced birefringence in dye-doped blue phase liquid crystals. Issue 6 (3rd May 2019) - Lin, Fen-Chi; Kuo, Hui-Ying; Huang, Shuan-Yu; Wu, Tse-Hsien; Lin, Jia-De; Lee, Chia-Rong
ABSTRACT: This paper investigates the photoinduced change of refractive index in dye (methyl red, MR)-doped blue phase (DDBP) cells by illumination of a pump beam. Through excitation of light irradiation with proper photon energy, MR can transform from trans -state to cis -state and successively diffuse and anisotropically adsorb on the inner glass substrate of the DDBP cell along the direction perpendicular to the polarisation of the pump beam. The adsorbed MR molecules can effectively rotate the orientation of the liquid crystal (LC) molecules and thereby modulate the effective refractive index of the DDBP cell. The SEM images of the adsorbed regions of the illuminated DDBP samples were also taken for discussing the relation between the pump intensity and the photoinduced birefringence. Graphical Abstract: